Assessing The Potential of Folic Acid to Mitigate Histopathological Damage in Channa Fish Under Allura Red-Induced Stress - Acharya, Supriyo; Chaudhari, Paramesh (Journal of Neonatal Surgery, 2025)
Background: Environmental stress in both wild and aquaculture conditions is faced by Channa fish. Chemical stressor, such as Allura Red, a synthetic dye, was reported to have toxicological effects on aquatic organisms. This study explores the potential protective role of folic acid against histopathological damages caused by Allura Red stress in Channa fish. Methods: tudy employed a controlled experiment where Channa fish were subjected to different concentrations of Allura Red, then supplemented with folic acid. Tissue damage in gills, liver, and kidneys was determined by histopathological analyses. Results: The results indicated that there were histopathological alterations in tissues exposed to Allura Red, including necrosis and inflammation in the gills and liver. However, folic acid treatment showed a marked reduction in these damages, restoring the integrity of the tissues. The analysis also included statistical comparison of tissue damage scores across different experimental groups... Conclusion: The results suggest that folic acid possesses therapeutic potential in countering the toxic effects of Allura Red stress on Channa fish. Such results may have further implications in the management of aquaculture and aquatic ecosystem health management.